Short-Range Demonstrations of Monocular Passive Ranging Using O2 (X3Σg− → b1Σ+g) Absorption Spectra. Issue 5 (May 2013) - Hawks, Michael R.; Vincent, R. Anthony; Martin, Jacob; Perram, Glen P.
The depth of absorption bands in observed spectra of distant, bright sources can be used to estimate range to the source. Experimental results are presented based on observations of the O2 X(v″ = 0) → b(v′ = 0) absorption band centered around 762 nm and the O2 X(v″ = 0) → b(v′ = 1) band around 689 nm. Range is estimated by comparing observed values of band-average absorption against predicted curves derived from either historical data or model predictions. Accuracy of better than 0.5% was verified in short-range (up to 3 km), static experiments using a high-resolution (1 cm −1 ) spectroradiometer. This method was also tested against the exhaust plume of a Falcon 9 rocket launched from Cape Canaveral, Florida. The rocket was launched from an initial range of 13 km and tracked for 90 s after ignition. Range error was below 2% for the first 30 s and consistent with predicted error throughout the track.